Thermistor behaviour and electric conduction analysis of Ni-doped niobate ferroelectric: the role of multiple beta parameters - Lanfredi, Silvania [UNESP]; Palacio, Gustavo [UNESP]; Bellucci, Felipe S. [UNESP]; Colin, Claire V.; Nobre, Marcos Augusto Lima [UNESP] (Iop Publishing Ltd, 2012)
A new engineered non-stoichiometric niobate ceramic with a tetragonal tungsten bronze (TTB)-type structure is prepared by non-isovalent substitution at the niobium backbone. The compound's formula is KSr2(Ni0.75Nb4.25)O-15 (delta), with space group equal to P4bm (#100), a polar group. Electrical properties of this new ferroelectric-semiconductor ceramic are investigated by impedance spectroscopy in the temperature range from 453 up to 953 K. The curve of the resistance as a function of temperature presents further characteristics of a temperature sensor with a negative temperature coefficient (NTC). At high temperatures, the analysis of electrical parameters shows an NTC behaviour ceramic with three distinct thermistor characteristic parameters, beta. The values of the beta parameter change from 9.82 x 10(3) to 1.29 x 10(4) K, while the temperature coefficient of resistance a changes from -0.047 to -0.023K(-1). The NTC behaviour of KSr2(Ni0.75Nb4.25)O15-delta is compared with the behaviour of some dielectric and other ferroelectric semiconductors. beta dependence with dc or the ac conductivity mechanism and its correlation with beta quality are discussed.